Efficacy and Safety of Transcatheter Arterial Chemoembolization Combined with Lenvatinib Plus Anti-PD-1 Inhibitors for Hepatocellular Carcinoma Patients with Extrahepatic Metastases: A Multicenter Retrospective Study - Liu DY; Li YN; Wu JY; Zeng ZX; Fu YK; Li H; Ou XY; Zhang ZB; Wang SJ; Wu JY; Yan ML (Journal of Hepatocellular Carcinoma)
De-Yi Liu,1,* Yi-Nan Li,1,* Jia-Yi Wu,1,2 Zhen-Xin Zeng,1 Yang-Kai Fu,1 Han Li,1 Xiang-Ye Ou,1 Zhi-Bo Zhang,3 Shuang-Jia Wang,4 Jun-Yi Wu,1,2 Mao-Lin Yan1,2 1Shengli Clinical Medical College of Fujian Medical University, Fuzhou, Fujian Province, People’s Republic of China; 2Department of Hepatobiliary Pancreatic Surgery, Fujian Provincial Hospital, Fuzhou, Fujian Province, People’s Republic of China; 3Department of Hepatopancreatobiliary Surgery, The First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian Province, People’s Republic of China; 4Department of Hepato-Biliary-Pancreatic and Vascular Surgery, The First Affiliated Hospital of Xiamen University, Xiamen, Fujian Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun-Yi Wu; Mao-Lin Yan, The Shengli Clinical Medical College of Fujian Medical University, Department of Hepatobiliary Pancreatic Surgery, Fujian Provincial Hospital, Dongjie Road 134, Fuzhou, Fujian Province, 350001, People’s Republic of China, Tel +86 591-88217130 ; +86 591-88217140, Fax +86 591-87557768, Email 1248087863@qq.com; yanmaolin74@163.comPurpose: The prognosis of hepatocellular carcinoma (HCC) with extrahepatic metastases (EM) is poor. The efficacy and safety of transcatheter arterial chemoembolization combined with lenvatinib plus anti-programmed cell death 1 inhibitors (triple therapy) for HCC with EM remains unclear. In this study, we aimed to determine the efficacy and safety of triple therapy in HCC patients with EM.Patients and Methods: This study retrospectively reviewed HCC patients with EM who received triple therapy and analyzed their survival rate using the Kaplan–Meier method. Univariate prognostic analysis of each data point was performed using the Log rank test, and multivariate prognostic analysis was performed using the Cox proportional risk regression model.Results: Among 60 HCC patients with EM who underwent triple therapy, the most common sites of metastasis were as follows (in descending order): the lungs (n=27), lymph nodes (n=22), and bones (n=10). After triple therapy, the median progression-free survival and median overall survival were 6 and 18.63 months, respectively. The 6-month, 1-year, and 2-year cumulative survival rates were 87.7%, 68.6%, and 26.8%, respectively. In the multivariate analysis, neutrophil-to-lymphocyte ratio (NLR) ≥ 4 and alpha-fetoprotein (AFP) level ≥ 400 ng/mL were independently associated with overall survival.Conclusion: Our findings revealed that triple therapy is an effective, well-tolerated regimen for HCC patients with EM. AFP level and NLR are prognostic risk factors for triple therapy in this patient population.Keywords: hepatocellular carcinoma, transcatheter arterial chemoembolization, lenvatinib, alpha-fetoprotein, neutrophil-to-lymphocyte ratio